IMPLEMENTING BLOOM’S TAXONOMY IN THE ENGLISH CURRICULUM UNDER MERDEKA BELAJAR PROGRAM - Edi, Syamsi; Iswandini, Iswandini; Andriani, Novi; Aryaningsih, Nur (English Review: Journal of English Education, 2024)
Education in Indonesia in the 5.0 era utilizes the MBKM English Education Curriculum, which is a modification of the 2013 English Education Curriculum. According to the 2019 PISA survey, Indonesia ranked 74th out of 79, indicating that the cognitive development of Indonesian children remains relatively low. The "Merdeka Belajar" (Independent Learning) strategy is a transformative step in education aimed at producing superior Indonesian human resources who embody the Pancasila student profile. This concept of independent learning emphasizes the cognitive growth of students, requiring them to think critically using their logical abilities. Bloom's Taxonomy can be interpreted as a hierarchical structure that classifies learning capabilities from the lowest to the highest levels. The cognitive, psychomotor, and affective elements are included in Bloom's three categories to categorize human learning activities. Students' intellectual capacities are developed within the cognitive domain, their skills within the psychomotor domain, and their attitudes and behaviors within the emotional domain. The problem formulation that the researcher will examine involves the implementation, factors, and impacts of Bloom's Taxonomy in the application of the MBKM English Education Curriculum in University institutions. This research employs a descriptive qualitative method, which is divided into three stages: data reduction, data presentation, and verification.